Analysis of the Effect of Work Compensation, Work Discipline and Motivation on Productivity of Employess On Tanggerang City - Luthfi Maryandi (Faculty of Economics and Business | Universitas Diponegoro, 2021)
This research was conducted to examine the effect of compensation, work discipline, and motivation on employee productivity.this research was conducted at PT Midi Utama Indonesia Tbk. this study is multiple linear regression. The results of this study are (1) compensation has a positive and significant effect on employee productivity (2) work discipline has a positive and significant effect on employee productivity (3) motivation has a positive and significant effect on employee productivity.